DAMPAK PENDIDIKAN ETIKA BISNIS SEBAGAI PONDASI PENGEMBANGAN PROFESIONALISME MAHASISWA AKUNTANSI PADA ERA GLOBALISASI DI UNIVERSITAS SURABAYA - Kristiana Greta Calosa; Nur Fitroten Dian Sari; Marcella Aulia Jayadi; Ayu Asari; Tries Ellia Sandari (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
Business ethics education plays a crucial role in shaping the professionalism of accounting students, particularly in addressing ethical challenges in the globalization era. This study aims to analyze the impact of business ethics education on the development of professional attitudes among accounting students at the University of Surabaya. Using a descriptive qualitative method, data were collected from 100 respondents who had completed a business ethics course. The findings indicate that business ethics education significantly helps students understand the principles of transparency, accountability, and integrity, despite challenges such as limited in-depth understanding and social pressures from their environment. These results underscore the importance of strengthening applied business ethics curricula and institutional support to enhance student professionalism.